Forecast of Biotechnology Trends in the World and in Ukraine Based on Analysis of Publications and Patents - Poliakova, O.Yu.; Shlykova, V.O.; Buntov, I.Yu. (Наука та інновації, 2019)
Introduction. Modern biotechnology is among the top priorities in every advanced economy. Problem Statement. Successful management of technology development requires an unbiased analysis of scholarly research results and their forecasting. The correspondence of technological development to the world trends plays an important role in ensuring the economy’s competitiveness. Purpose. The purpose of the study is to determine the world trends in scholarly research and developments in the field of biotechnology, as well as the correspondence of the situation in Ukraine to the world trends. Materials and Methods. Bibliometric and patent analysis is one of the most common tools for analyzing the current state, promising directions of scholarly research and commercial use. This research presents the results of analysis of the world and Ukrainian trends in publication and patent activities in the sphere of biotechnology for 2000—2015, as well as forecasts for 2016—2019. The trend models have been constructed for forecasting. Biotechnology-related publications of SCImago Journal & Country Rank portal, Science Direct database, and Vernadsky National Library of Ukraine abstract database, as well as patents of the World Intellectual Property Organization database have been used. Results. The forecast results have shown an upward tendency in the global amount of publications and patents in biotechnology, in the coming years. In all areas of biotechnology, the share of Ukrainian publications in the global space of biotechnological research is extremely small. Among the analyzed areas, the largest forecasted share of Ukrainian origin publications in international databases belongs to Materials Science — Biomaterials and amounts to 0.3% on the global sca le. The patenting of Ukrainian developments at the international level, provided the existing trend is maintained, will also remain at a very low level (0.05% on a global scale). China and the USA, which have a share of 33.1 and 24.9%, respectively, will keep leadership in this direction The total number of patents belonging to the EU Member States (28) will reach about 18.1%. Conclusions. For today, Ukraine has certain advantages in the development of biotechnology in the field of agriculture, which can become the basis for the development of national bioeconomy. Consequently, in the agricultural sector, state support is needed to implement the existing developments by encouraging business. At the same time, in the medical field, there is a significant gap between Ukraine and the leading countries, thus the government should focus efforts on supporting research in this area in order to make its results ready for patenting. Вступ. Сучасні біотехнології є однією з найбільш пріоритетних галузей національної економіки розвинених країн. Проблематика. Успішне управління розвитком технологій вимагає об'єктивного аналізу результатів наукових досліджень та їх прогнозування. Відповідність рівня технологічного розвитку країни світовим тенденціям відіграє важливу роль у забезпеченні конкурентоспроможності її економіки. Мета. Визначення тенденцій наукових досліджень і розробок у галузі біотехнологій та їх відмінностей в світі й Україні. Матеріали й методи. Бібліометричний та патентний аналіз використано як найпоширеніші інструменти аналізу поточного стану, перспективних напрямів наукових досліджень і комерціалізації їх результатів. Аналіз світових та українських тенденцій публікаційної та патентної активності у сфері біотехнології за 2000—2015 рр., а також прогнозуван ня на 2016—2019 рр. з використанням трендових моделей. Роботу здійснено на основі публікацій, пов'язаних з біотехнологіями, що містяться на порталі SCImago Journal & Country Rank, у базі Science Direct та реферативній базі даних Національної бібліотеки України ім. В.І. Вернадського, а також патентів з бази даних World In tel lectual Proper ty Organization. Результати. Прогнозування демонструє тенденцію до збільшення обсягу публікацій та патентів у галузі біотехнології у світі в найближчі роки. За всіма напрямами біотехнології питома вага українських публікацій у світовому просторі біотехнологічних наукових досліджень є вкрай малою. Серед аналізованих напрямів найбільша прогнозована питома вага публікацій українського походження у міжнародних базах визначена за напрямом «Матеріалознавство – біоматеріали» і становить 0,3 % у загальносвітовому масштабі. Патентування українських розробок на міжнародному рівні, за умов збереження наявного тренду, також залишатиметься на дуже низькому рівні, а саме 0,05 % у світовому масштабі. Лідерство за цим напрямом зберігатиметься за Китаєм та США із частками 33,1 та 24,9 % відповідно, загальна кількість патентів країн ЄС становитиме близько 18,1 %. Висновки. На сьогодні Україна має певні переваги у розвитку біотехнологій у галузі сільського господарства, які можуть стати основою для розвитку біоекономіки країни. Отже, в аграрній сфері необхідною є державна підтримка впровадження наявних розробок шляхом заохочення бізнесової діяльності. У той же час у медицині спостерігається значне відставання від провідних країн світу, тому зусилля держави повинні зосереджуватися на підтримці проведення досліджень у цій галузі та доведення розробок до стадії готовності для патентування. Введение. Современные биотехнологии являются одним из приоритетных секторов национальной экономики для развитых стран мира. Проблематика. Успешное управление развитием технологий требует объективного анализа результатов научных исследований и их прогнозирования. Соответствие уровня технологического развития страны мировым тенденциям играет важную роль в обеспечении конкурентоспособности экономики. Цель. Определение тенденций научных исследований и разработок в области биотехнологии и их отличий в мире и Украине. Материалы и методы. Библиометрический и патентный анализ использованы как наиболее распространенные инструменты анализа текущего состояния, перспективных направлений научных исследований и коммерциализации их результатов. Анализ мировых и украинских тенденций публикационной и патентной активности в сфере биотехнологии за 2000—2015 гг., а также прогнозирование на 2016—2019 гг. с использованием трендовых моделей. Роботу проводили на основании публикаций, связанных с биотехнологиями, размещенных на портале SCImago Journal & Country Rank, базы Science Direct и реферативной базы данных Национальной библиотеки Украины им. В.И. Вернадского, а также патентов в базе данных World Intellectual Property Organization. Результаты. Прогнозирование демонстрирует тенденцию к увеличению количества публикаций и патентов в сфере биотехнологий в мире в ближайшие годы. По всем направлениям биотехнологии удельный вес украинских публикаций в мировом пространстве биотехнологических научных исследований крайне низок. Среди проанализированных направлений самый высокий спрогнозированный удельный вес имеют публикации украинского происхождения в международных базах по направлению «Материаловедение — биоматериалы», который составляет 0,3 % в общемировом масштабе. Патентование украинских разработок на международном уровне, при сохранении имеющегося тренда, также будет оставаться на очень низком уровне, а именно 0,05 % в мировом масштабе. Лидерами по этому направлению останутся Китай и США с долями 33,1 и 24,9 % соответственно, общее количество патентов стран ЕС составит около 18,1 %. Выводы. На сегодня Украина имеет определенные преимущества в развитии биотехнологий в области сельского хозяйства, которые могут стать основой для развития биоэкономики страны. Таким образом, в аграрной сфере необходима государственная поддержка внедрения имеющихся разработок путем поощрения бизнеса. В то же время в медицине наблюдается существенное отставание от ведущих стран мира, поэтому усилия государства должны быть сосредоточены на поддержке проведения исследований в этой области и доведения разработок до стадии готовности к патентованию.